Perancangan dan Integrasi Smart Touch Presenter Kit-Portable Interactive Surface dalam pembelajaran Hybrid Learning System - Ashadi, Imam; Basuki, Achmad; Dewantara, Bima Sena Bayu (The Indonesian Journal of Computer Science, 2022)
The health crisis caused by the covid-19 virus outbreak has given birth to online learning in all parts of the world until the covid-19 pandemic ends, so that in this condition the government urges the government to innovate and adapt related to the use of available technology to support the learning process. All elements in learning such as teachers, lecturers and students are required to carry out a large-scale transmission that has never been done before from conventional learning (offline) to online-based learning. Some of the obstacles that often occur are caused by inadequate IT learning support infrastructure so that there is a range of learning losses. For this reason, learning IT devices that are cheap, ergonomic and fulfill all aspects of learning are carried out to solve the problems in this research, thus this paper proposes a device, namely smart projection low-cost interactive surface (SP-LCIS) as one of the solutions for supporting devices in implementation of Hybrid Learning System learning. In this research observation conducted at SMKN 3 Jember it was found that 99% of the devices run very well and provide added value in learning and 1% feel that they increase their preparation time, such as having to learn how to operate them effectively.